2023
DOI: 10.1245/s10434-023-13141-y
|View full text |Cite
|
Sign up to set email alerts
|

Locally Recurrent Rectal Cancer: Toward a Second Chance at Cure? A Population-Based, Retrospective Cohort Study

Abstract: Background In current practice, rates of locally recurrent rectal cancer (LRRC) are low due to the use of the total mesorectal excision (TME) in combination with various neoadjuvant treatment strategies. However, the literature on LRRC mainly consists of single- and multicenter retrospective cohort studies, which are prone to selection bias. The aim of this study is to provide a nationwide, population-based overview of LRRC after TME in the Netherlands. Patients and Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…And the prognosis for patients with recurrent pelvic disease is poor. According to a recent published literature, the mean survival time was only 23.9 months for locally recurrent rectal cancer patients with prior neoadjuvant radiotherapy [22]. For those who undergone curative-intent treatment, the 3-year OS was 70%; For those who received palliative treatment or best supportive care, the 3-year OS was only 10-20% [22].…”
Section: Discussionmentioning
confidence: 99%
“…And the prognosis for patients with recurrent pelvic disease is poor. According to a recent published literature, the mean survival time was only 23.9 months for locally recurrent rectal cancer patients with prior neoadjuvant radiotherapy [22]. For those who undergone curative-intent treatment, the 3-year OS was 70%; For those who received palliative treatment or best supportive care, the 3-year OS was only 10-20% [22].…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies demonstrated that 5.6–6.4% of rectal cancer patients experience local recurrence during their follow-up and up to 41–44.9% of these patients have metastases 11 , 12 . Excluding patients with known distant metastases, approximately 30% of patients with LRRC have indeterminate lung nodules observed at diagnosis 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Dear Editor, Locally recurrent rectal cancer (LRRC) occurs in 4%-11% of patients receiving curative treatment for primary rectal cancer [1,2]. For some patients with LRRC, there remains the possibility of further radical surgery and the ability to achieve a complete resection is paramount to ensure optimal patient outcomes.…”
Section: Laparoscopic Resection For Locally Recurrent Rectal Cancer-a...mentioning
confidence: 99%
“…For some patients with LRRC, there remains the possibility of further radical surgery and the ability to achieve a complete resection is paramount to ensure optimal patient outcomes. Previous research has reported that curative treatment and margin-free resection confers a survival advantage [2,3]. With complex pelvic anatomy, extent of tumour growth, fibrosis etc.…”
Section: Laparoscopic Resection For Locally Recurrent Rectal Cancer-a...mentioning
confidence: 99%
See 1 more Smart Citation